Eksistensi Mawah di Aceh: Analisis Habitus, Modal, dan Maqashid Syariah - Fitri Maghfirah; Faisal Faisal; Fauzah Nur Aksa; Fitria Mardhatillah (Isti`dal : Jurnal Studi Hukum Islam, 2023)
This article describes the discourse on Mawah culture in Aceh, namely about why the concept of mawah continues to exist among the people of Aceh and what are the implications of mawah practice for mawah practitioners. This study is a field research conducted based on qualitative methods and a socio-legal approach. Data reviews are examined from interviews, observations, and previous studies and information from the media. In analyzing the discourse in this article, the author uses the capital and habitus theory framework from Pierre Bourdiue and the maqashid sharia theory from Jasser Auda. The results of this study indicate that, mawah is a habitus that continues to exist and is practiced by the people of Aceh, the existence of mawah is also supported by the arena and capital owned by the parties, both cultural, social and economic capital. In addition, the vacancy of cultural capital can also be a driving factor for the practice of mawah. Meanwhile, the continued existence of mawah practices can also be influenced by the realization of mawah's objectives and the benefits that will be obtained by the people of Aceh. Borrowing an analytical knife in maqāshid al-'ammah, then there is the placement of soul safety (Hifz al-nafs) as the main basis for the purpose of establishing an Islamic economy that is just and has the principle of helping each other. Meanwhile in maqāshid al-khassah (special purpose), this represents the existence of hifz al-māl, where with the concept of mawah, the productivity of an asset is more optimal. Furthermore, within the reach of maqāshid juziyyah (partial goal), the practice of mawah also contains the aim of strengthening and developing the economies of the parties through the realization of maqāshid protecting assets (hifz al-māl), whether it is protecting the assets of the owner of the mawah object as an investor or as an effort to strengthen the economy of the mawah object manager.